TET enzyme driven epigenetic reprogramming in early embryos and its implication on long-term health - Montgomery, Ty; Uh, Kyungjun; Lee, Kiho (Frontiers in Cell and Developmental Biology, 2024)
Mammalian embryo development is initiated by the union of paternal and maternal gametes. Upon fertilization, their epigenome landscape is transformed through a series of finely orchestrated mechanisms that are crucial for survival and successful embryogenesis. Specifically, maternal or oocyte-specific reprogramming factors modulate germ cell specific epigenetic marks into their embryonic states. Rapid and dynamic changes in epigenetic marks such as DNA methylation and histone modifications are observed during early embryo development. These changes govern the structure of embryonic genome prior to zygotic genome activation. Differential changes in epigenetic marks are observed between paternal and maternal genomes because the structure of the parental genomes allows interaction with specific oocyte reprogramming factors. For instance, the paternal genome is targeted by the TET family of enzymes which oxidize the 5-methylcytosine (5mC) epigenetic mark into 5-hydroxymethylcytosine (5hmC) to lower the level of DNA methylation. The maternal genome is mainly protected from TET3-mediated oxidation by the maternal factor, STELLA. The TET3-mediated DNA demethylation occurs at the global level and is clearly observed in many mammalian species. Other epigenetic modulating enzymes, such as DNA methyltransferases, provide fine tuning of the DNA methylation level by initiating de novo methylation. The mechanisms which initiate the epigenetic reprogramming of gametes are critical for proper activation of embryonic genome and subsequent establishment of pluripotency and normal development. Clinical cases or diseases linked to mutations in reprogramming modulators exist, emphasizing the need to understand mechanistic actions of these modulators. In addition, embryos generated via in vitro embryo production system often present epigenetic abnormalities. Understanding mechanistic actions of the epigenetic modulators will potentially improve the wellbeing of individuals suffering from these epigenetic disorders and correct epigenetic abnormalities in embryos produced in vitro. This review will summarize the current understanding of epigenetic reprogramming by TET enzymes during early embryogenesis and highlight its clinical relevance and potential implication for assisted reproductive technologies.